Characterization of pPCP1 Plasmids in Yersinia pestis Strains Isolated from the Former Soviet Union - Chythanya Rajanna; Tamara Revazishvili; Mohammed H. Rashid; Svetlana Chubinidze; Lela Bakanidze; Shota Tsanava; Paata Imnadze; Kimberly A. Bishop-Lilly; Shanmuga Sozhamannan; Henry S. Gibbons; J. Glenn Morris; Alexander Sulakvelidze (International Journal of Microbiology)
Complete sequences of 9.5-kb pPCP1 plasmids in three Yersinia pestis strains from the former Soviet Union (FSU) were determined and compared with those of pPCP1 plasmids in three well-characterized, non-FSU Y. pestis strains (KIM, CO92, and 91001). Two of the FSU plasmids were from strains C2614 and C2944, isolated from plague foci in Russia, and one plasmid was from strain C790 from Kyrgyzstan. Sequence analyses identified four sequence types among the six plasmids. The pPCP1 plasmids in the FSU strains were most genetically related to the pPCP1 plasmid in the KIM strain and least related to the pPCP1 plasmid in Y. pestis 91001. The FSU strains generally had larger pPCP1 plasmid copy numbers compared to strain CO92. Expression of the plasmid's pla gene was significantly (P≤.05) higher in strain C2944 than in strain CO92. Given pla's role in Y. pestis virulence, this difference may have important implications for the strain's virulence.